Diversity of Fungal Colonization in Respiratory Tract of NaÃ¯ve Lung Cancer and The Emergence of Voriconazole Resistant Aspergillus - Jamal Zaini; Abul A'la Al Maududi; Zahrah Annisa; Denny Grecius Siregar; Findra Setianingrum; Mulyati Tugiran; Ridhawati Sjam; Robiatul Adawiyah; Anna Rozaliyani; Sita Andarini; Elisna Syahruddin (HAYATI Journal of Biosciences, 2023)
Fungal spores in the air can be inhaled and enter the human respiratory tract. The entry of fungi into the respiratory tract can cause colonization or infection depending on the host immune response. Fungal colonization is the first step into debilitating fungal disease in humans, especially in immunocompromised groups. The increased rate of drug-resistant fungi has been reported in human disease and the environment. This study aims to examine the diversity of fungal colonization in humans and the rate of fungal resistance to voriconazole. This cross-sectional study was done in patients with naÃ¯ve lung cancer who had not been previously treated with any cancer therapy nor given antifungal agent. Induced sputum from 70 subjects was collected and inoculated in the Sabouraud Dextrose Agar medium. Macroscopic and microscopic examinations were performed to identify fungal species. Voriconazole susceptibility tests were done using the disc diffusion method. This study found Candida albicans, Aspergillus niger, Aspergillus fumigatus, and Penicillium sp. among the most common lower respiratory tract colonies. This study also found the colonization of up to 5 species in a single subject. A high rate of voriconazole-resistant Aspergillus sp. was found (42.4%) among 59 isolates tested. Given that these subjects had never taken antifungal agents previously, the high rate of voriconazole resistance might be attributed to the environment, such as community and agriculture. Mitigation of antifungal use in the agricultural sector, fungal diversity in the environment, and clinical study of fungal colonization/ infection in other high-risk groups are needed.